2012
DOI: 10.1111/jen.12010
|View full text |Cite
|
Sign up to set email alerts
|

Western corn rootworm adult captures as a tool for the larval damage prediction in continuous maize

Abstract: Continuous maize production in Croatia and Central Europe is at serious risk from western corn rootworm (WCR) (Diabrotica virgifera virgifera, LeConte) activity. When alternatives to sowing continuous are not feasible, farmers will need a reliable tool that will allow them to choose fields for continuous cultivation. The decision could be based on assessing the adult populations in fields from the previous year. Non-baited yellow sticky traps [Pherocon AM (PhAM)] could be utilized as a practical tool for sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Both USA and European authors have demonstrated that there is a correlation between the number of adults captured by yellow sticky traps (i.e. PhAM) and plant damage the following year (Blandino et al 2014 ; Boriani 2006 ; Hein and Tollefson 1985 ; Kos et al 2014 ). The US authors stated that economic thresholds would be exceeded when more than 40 beetles/PhAM trap/week (6 beetles/PhAM trap/day) were caught the previous year in one period (ca.…”
Section: Case Studies Of Alternative Pest Management In Maizementioning
confidence: 99%
See 1 more Smart Citation
“…Both USA and European authors have demonstrated that there is a correlation between the number of adults captured by yellow sticky traps (i.e. PhAM) and plant damage the following year (Blandino et al 2014 ; Boriani 2006 ; Hein and Tollefson 1985 ; Kos et al 2014 ). The US authors stated that economic thresholds would be exceeded when more than 40 beetles/PhAM trap/week (6 beetles/PhAM trap/day) were caught the previous year in one period (ca.…”
Section: Case Studies Of Alternative Pest Management In Maizementioning
confidence: 99%
“…In Italy, the threshold was 42 beetles/PhAM trap/day on average over a 6-week period after the beginning of adult flights (Boriani 2006 ; Blandino et al 2014 ). In Croatia, the threshold was estimated at 41 adults/ PhAM trap in week 31 (Kos et al 2014 ). Economic thresholds can greatly vary with climatic/agronomic conditions and prices of maize and insecticides (Oleson et al 2005 ).…”
Section: Case Studies Of Alternative Pest Management In Maizementioning
confidence: 99%
“…Instead, European maize growers in highly infested areas began to apply insecticides against D. v. virgifera larvae to prevent yield losses. Various traps can be utilized for sampling WCR adults to determine the previous year's adult population and to take action based on established thresholds (Kos et al 2014). Foliar insecticides targeting the adult beetles are only occasionally applied, mainly because of high costs and limited efficacy but also because they could interfere with integrated and biological-based management options already in place against other European maize pests, for example the European corn borer.…”
Section: Introductionmentioning
confidence: 99%
“…Thresholds have been defined for wireworms (Furlan 2014 ), brown planthopper (Zheng et al 2007 ) and for different cotton pests, including A. gossypii (Silvie et al 2013 ; Sequeira and Naranjo 2008 ). Data input for DSS are regularly collected through field-level monitoring: WCR and wireworms can be monitored using sticky traps, pheromone traps or bait traps (Sufyan et al 2011 ; Vuts et al 2014 ; Benefer et al 2012 ; Parker 1994 , 1996 ; van Herk and Vernon 2013 ; Tóth et al 2002 ; Tóth et al 2007 ; Vuts et al 2012 ; Tóth 2013 ; Tóth et al 2015 ; Furlan et al 2017a , 2017b ; Bažok et al 2011 ; Kos et al 2014 ). In Northern Italy (Emilia-Romagna region) a monitoring net for two wireworm species has been employed in 2017 and 2018 using about 1100 pheromone traps per year, providing provisional threshold to alert farmers on infestation risk.…”
Section: Resultsmentioning
confidence: 99%